Synergistic Potential of the Leaves of Aspillia africana (Compositae) and Psidium guajava (Myrtaceae) Against Some Selected Bacterial and Fungal Isolates - Foluso Ologundudu; OLADELE IDRIS (Faculty of Medicine, Diponegoro University, 2020)
Background: The plethora of secondary metabolites inherent in plants that could be synthesized and formulated into useful drugs for the treatment of diseases is not fully understood. This study was carried out to evaluate the antimicrobial potential of the leaves of Aspillia africana and Psidium guajava plants on some selected bacterial and fungal isolates.Methodology: Fresh and matured leaves of Aspillia africana and Psidium guajava were collected at the Federal College of Agriculture, Akure and Obafemi Awolowo University (OAU), Ile-Ife. The plants were identified and voucher deposited at the Herbarium unit of the Department of Botany, Obafemi Awolowo University, Ile-ife. The pure isolates of the bacteria and fungi were obtained from Department of Microbiology, Obafemi Awolowo University, Ile-Ife, Nigeria. The bacteria isolates were maintained on nutrient agar slant and the fungal isolates on PDA. Extraction of the plant materials using methanol, ethanol and aqueous fractions were carried out using standard protocols. The isolates were inoculated on a nutrient broth. Minimum Inhibitory Concentration (MIC) of the extracts was determined by broth dilution method while minimal bactericidal and fungicidal concentrations respectively were determined following established protocols.Results: The results showed that Bacillus cereus, Cornybacterium pyogenes, Klebsiella pneumonia and Escherichia coli were all resistant to the plant extracts. The fungal isolates; Candida albicans, Tryptophyton rubrum, Penicillium expansium, and Aspergillus flavus were resistant to Psidium guajava extract as no significant activity was observed. All the plant extracts produced considerable antimicrobial activities with Streptococcus faecalis and Staphyloccocus. aureus. whereas, these organisms were resistant to ofloxacin, sparfloxacin, chloramphenicol, augmentin, ciprofloxacin and septrin.Conclusion: This study revealed that the therapeutic properties of Aspillia africana and Psidium guajava are better enhanced with their synergistic potential to the tested microorganisms.Keywords: Aspillia africana; Bactericidal; Psidium guajava; Synergistic;therapeutic.Background: The plethora of secondary metabolites inherent in plants that could be synthesized and formulated into useful drugs for the treatment of diseases is not fully understood. This study was carried out to evaluate the antimicrobial potential of the leaves of Aspillia africana and Psidium guajava plants on some selected bacterial and fungal isolates.Methodology: Fresh and matured leaves of Aspillia africana and Psidium guajava were collected at the Federal College of Agriculture, Akure and Obafemi Awolowo University (OAU), Ile-Ife. The plants were identified and voucher deposited at the Herbarium unit of the Department of Botany, Obafemi Awolowo University, Ile-ife. The pure isolates of the bacteria and fungi were obtained from Department of Microbiology, Obafemi Awolowo University, Ile-Ife, Nigeria. The bacteria isolates were maintained on nutrient agar slant and the fungal isolates on PDA. Extraction of the plant materials using methanol, ethanol and aqueous fractions were carried out using standard protocols. The isolates were inoculated on a nutrient broth. Minimum Inhibitory Concentration (MIC) of the extracts was determined by broth dilution method while minimal bactericidal and fungicidal concentrations respectively were determined following established protocols.Results: The results showed that Bacillus cereus, Cornybacterium pyogenes, Klebsiella pneumonia and Escherichia coli were all resistant to the plant extracts. The fungal isolates; Candida albicans, Tryptophyton rubrum, Penicillium expansium, and Aspergillus flavus were resistant to Psidium guajava extract as no significant activity was observed. All the plant extracts produced considerable antimicrobial activities with Streptococcus faecalis and Staphyloccocus. aureus. whereas, these organisms were resistant to ofloxacin, sparfloxacin, chloramphenicol, augmentin, ciprofloxacin and septrin.Conclusion: This study revealed that the therapeutic properties of Aspillia africana and Psidium guajava are better enhanced with their synergistic potential to the tested microorganisms.